Latent Class Modeling with A Time-To-Event Distal Outcome: A Comparison of One, Two and Three-Step Approaches. Issue 1 (2nd January 2019) - Lythgoe, Daniel T.; Garcia-Fiñana, Marta; Cox, Trevor F.
Abstract : Latent class methods can be used to identify unobserved subgroups which differ in their observed data. Researchers are often interested in outcomes for the identified subgroups and in some disciplines time-to-event outcome measures are common, e.g., overall survival in oncology. In this study Monte Carlo simulation is used to evaluate the empirical properties of latent class effect estimates on a time-to-event distal outcome using one, two and three-step approaches. Both standard and inclusive bias-corrected three-step approaches are considered. One-step latent class effect estimates are shown to be superior to the evaluated alternatives. Both the two-step approach and a standard three-step approach, where subjects are partially assigned to latent classes, produced unbiased estimates with nominal confidence interval coverage when latent classes were well separated, but not otherwise. Keywords : latent class analysis, time-to-event, two-step, joint modeling